Implementation of Balanced Scorecard in public institutions: a brief bibliographic review (Research, Society and Development, 2020)
This article has as its main objective conduct a theoretical review about the application of the Balanced Scorecard, tool that translates strategic planning into operational actions, in public institutions, and how these results can contribute to increased efficiency in planning these organizations. It also seeks to contribute to the increase of the knowledge base on the topic. As a methodological strategy, a bibliographic research was performed about in works developed on the theme. When analyzing specific cases of Municipal Institute of Public Administration, Brazilian Airport Infrastructure Company, State Public Ministries, Public Ministry of Santa Catarina e São Paulo Department of Finance, it was concluded that the Balanced Scorecard, despite its limitations in the public sphere, had a strong impact on improving in the planning of these institutions and in the improvement of all your processes.